The Prognostic Impact of Pathology on Patients With Pseudomyxoma Peritonei Undergoing Debulking Surgery: A Systematic Review and Meta-Analysis of Retrospective Studies - Zhou, Shengnan; Zhao, Huaiyu; He, Xiaodong (Frontiers in Surgery, 2020)
Background: Pseudomyxoma peritonei (PMP) is a rare clinical condition characterized by the progressive accumulation of mucinous ascites and peritoneal implants with fatal outcomes. Some studies have reported the effect of PMP biology on patient outcome. The aim of this study was to analyse published studies focusing on the impact of pathology on the prognosis of PMP patients undergoing debulking. Methods: Data from all studies regarding the prognosis of patients with different pathologies who underwent debulking surgery were analysed. We searched PubMed, the Wiley Online Library, Ovid and the Cochrane Library (through January 2020). Studies were limited to those in English. Five studies were identified, and the differences in 5-year survival rates were analysed according to Kaplan-Meier survival curves. The hazard ratios (HRs) of the 5-year survival rates were calculated. Results: The mean and median 5-year survival rates of all patients were 39% and 40%, respectively. The median overall survival was 49.3 months. The mean 5-year survival rates of low-grade PMP was 45.2%. The 5 studies had sufficient data to calculate HRs from the 5-year survival rates data, and three had HRs lower than 1. The total HRs was 0.54, with a 95% CI between 0.33 and 0.89 (P = 0.01). Conclusions: Among PMP patients receiving debulking surgery who are not able undergo complete cytoreductive surgery, low-grade biological PMP had a better prognosis than high-grade PMP.